Event Quality Analysis Towards Visitors at Miyako Island Rock Festival Japan 2023 - Maranisya, Ulfi; Agustiaz, Tengku Maulidia Andaribi; Dewi, Liliani (Jurnal Penelitian Pariwisata, 2025)
This investigation seeks to elucidate the extent to which the determinants of service quality and event quality, as administered by festival organizers, impact the decision-making processes of attendees at the Miyako Island Rock Festival 2023. The Miyako Island Rock Festival, which has its origins in Japan, has been conducted annually since the year 2005. This research employed a sample comprising 357 respondents. Subsequently, the analytical methodology applied in this research involved the utilization of tests executed on SPSS version 26. The findings of this study reveal that service quality exerts a significant influence on the visiting decisions at the Miyako Island Rock Festival 2023, that event quality similarly impacts these decisions, and that both service quality and event quality serve as critical indicators of visiting decisions at the Miyako Island Rock Festival 2023. The conclusions drawn from this research underscore the necessity of enhancing services such as the provision of event information, maintenance of cleanliness, and assurance of security at the Miyako Island Rock Festival. Concurrently, the evaluation of the event concept for the Miyako Island Rock Festival, specifically regarding the service rendered by event crews and the performances by guest artists, possesses the potential to attract an increased number of visitors and to augment tourist attendance at Miyako Island. Keywords: event quality, Japan Festival, Miyako Island